Interpersonal Communication Model and Learning Readiness Among Santri in Achieving The Success of Study at Higher-Educational Institutions - Sholeh, Ahmad; Yaqien, Nurul (JURNAL AL-TANZIM, 2022)
This study aims to determine to what extent the education system of Islamic boarding schools (known as Pondok Pesantren) is related to the model of interpersonal communication and pesantren students (known as santri) readiness to learn can contribute to their success while taking the level in higher education. The authors used the quantitative method as the research approach. This research was conducted at the Pondok Pesantren "Anwarul Huda" Karang Basuki, Malang. To solve the problems in this study, two statistical analysis techniques were used, namely descriptive statistics and multiple regression analysis. The results of this study indicated that first, most of the santri studying at higher educational institutions (universities) had poor interpersonal communication, quite good learning readiness, and good learning outcomes. Second, the santri’s interpersonal communication model and learning readiness significantly contribute to university learning outcomes achievement by 7.6% and other factors that influence the rest. This analysis indicates that santri’s interpersonal communication and learning readiness have not been optimally carried out in Islamic boarding schools. Therefore, every educator should always provide directions to generate and develop santri’s interpersonal communication model and learning readiness to maximize their learning outcomes in higher education.